Macrodystrophia lipomatosis : a rare congenital anomaly - Singal, KK; Singal, N; Mehra, V; Singh, H; Kaur, J; Relan, P (Bangladesh Journal of Medical Science, 2013)
Macrodystrophia Lipomatosis is rare congenital hamartomatous enlargement of soft tissue components leading to gigantism of single, multiple digits or entire limb. Clinical findings are recognised as early as in neonatal period to late adulthood. Patients usually present for either cosmetic corrections or mechanical problems. We report a case of 8 year old female with progressive increase in size of left 2nd and 3rd toes. X-ray findings show congenital focal enlargement of soft tissues and bones of 2nd and 3rd toes and adjacent metatarsals. Clinical and radiological features of our patient points out towards this uncommon condition. DOI: http://dx.doi.org/10.3329/bjms.v12i4.13465 Bangladesh Journal of Medical Science Vol. 12 No. 04 October 13 Page 442-444